Výročí Josefa Thomayera - 85 let od smrti, 160 let od narození - Hlaváčková, Ludmila (Casopis lekaru ceskych, 2012)
Study summarises the life, work, pedagogical and popularization activities of Josef Thomayer on the basis of his publications and writings as well as archival sources.
Keywords: učebnice jako téma; vnitřní lékařství; Textbooks as Topic; Czechoslovakia; Austria-Hungary; Internal Medicine; dějiny 20. století; Rakousko-Uhersko; History, 20th Century; dějiny 19. století; Československo; History, 19th Century